2021
DOI: 10.1021/acs.jpcb.1c07137
|View full text |Cite
|
Sign up to set email alerts
|

Double Proton Transfer during a Novel Tertiary α-Ketol Rearrangement in Ketol-Acid Reductoisomerase: A Water-Mediated, Metal-Catalyzed, Base-Induced Mechanism

Abstract: (KARI) catalyzes the conversion of (S)-2-acetolactate or (S)-2-aceto-2-hydroxybutyrate to 2,3-dihydroxy-3-alkylbutyrate, the second step in the biosynthesis of branched chain amino acids (BCAAs). Because the BCAA biosynthetic pathway is present in bacteria, plants, and fungi, but absent in animals, it is an excellent target for the development of new-generation antibiotics and herbicides. Nevertheless, the mechanism of the KARI-catalyzed reaction has not yet been fully solved. In this study, we used iterative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Water-assisted proton transfer plays an essential role in lowering the reaction energy barrier in systems containing phosphotungstic acid, 44 amino acids, [45][46][47] and nucleic acid bases. 48 However, reports of reactions with water-assisted proton transfer are sparse for metal-bearing systems, [49][50][51][52][53] especially actinide metals. The mechanism identified here for Np(VI) reduction with HzPn involves a remarkable water-mediated proton transfer, which may contribute to further advances in separations of Np from U and Pu in spent fuel reprocessing.…”
Section: Introductionmentioning
confidence: 99%
“…Water-assisted proton transfer plays an essential role in lowering the reaction energy barrier in systems containing phosphotungstic acid, 44 amino acids, [45][46][47] and nucleic acid bases. 48 However, reports of reactions with water-assisted proton transfer are sparse for metal-bearing systems, [49][50][51][52][53] especially actinide metals. The mechanism identified here for Np(VI) reduction with HzPn involves a remarkable water-mediated proton transfer, which may contribute to further advances in separations of Np from U and Pu in spent fuel reprocessing.…”
Section: Introductionmentioning
confidence: 99%
“…There has been considerable interest in exploring the biocatalytic potential of NADH-dependent KARIs as they are desirable in industrial applications including anaerobic fermentation to produce branched-chain amino acid or biofuels. 19 The fact that MtKARI-II is a new NADH/NADPH bi-cofactor-dependent KARI suggested that this Mt variant may possess a considerable degree of evolutionary advantages because living cells usually contain higher levels of NADH.…”
Section: Resultsmentioning
confidence: 99%